Persepsi Siswa Terhadap Penggunaan Laboratorium Sebagai Sumber Belajar Siswa Kelas XI SMA Negeri 16 Medan - Ayu Riski Aulia; Syarifah Widya Ulfa; Fitriya Handayani; Qoyum Amalia; Rifqi Khoir Afdan (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This study aims to see how students view the laboratory as a learning resource. The main task of the laboratory is to conduct experiments to support biological concepts and enable the development of scientific methods in biology classes. XII Waterfall Village, Medan Marelan District, North Sumatra, 20256. The subjects used were students of class XI IPA 3. This study used a qualitative method involving language studies. However, according to data obtained from the results of the questionnaire, 92% of students in science class 3 among 37 subjects who answered the questionnaire said that placement in the lab could improve student learning outcomes. Laboratory learning has certain advantages compared to other learning methods. This means that students directly gain experience and skills in doing internships, increase student participation both individually and in groups, and students learn to understand the principles of the scientific method. Keywords: Perception, Laboratory, Learning Resources